Density-dependent Growth of Endangered Labeo bata (Hamilton, 1822) in Nursery Ponds (Journal of Environmental Science and Natural Resources, 2016)
The effect of stocking density on growth performance and survival rate of endangered Labeo bata, was conducted in nursery ponds from 14th June to 13th August, 2013. Three different stocking densities viz. 500, 600 and 700 piece-1 decimal were assigned as treatment T1, T2 and T3, respectively. The initial average weight of L. bata was 0.15±008 g. Hatchlings in all the nursery ponds were fed indigenous feed (26.95% crude protein) for 8 weeks. Temperature, ammonia nitrogen, pH had no significant differences (P